2019
DOI: 10.1136/bmjopen-2018-023390
|View full text |Cite
|
Sign up to set email alerts
|

A guided and unguided internet- and mobile-based intervention for chronic pain: health economic evaluation alongside a randomised controlled trial

Abstract: ObjectiveThis study aims at evaluating the cost-effectiveness and cost-utility of a guided and unguided internet-based intervention for chronic pain patients (ACTonPainguidedand ACTonPainunguided) compared with a waitlist control group (CG) as well as the comparative cost-effectiveness of the guided and the unguided version.DesignThis is a health economic evaluation alongside a three-arm randomised controlled trial from a societal perspective. Assessments were conducted at baseline, 9 weeks and 6 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
(68 reference statements)
1
20
0
Order By: Relevance
“…A recent randomized controlled trial (RCT) on an IMI based on Acceptance and Commitment Therapy (ACT) showed guided, but not unguided, IMIs being effective in improving pain interference (Cohen d =0.58 at posttreatment and follow-up, respectively [ 22 ]) in individuals with chronic, nonmalignant pain for 6 months or longer. Moreover, changes in psychological flexibility mediated all outcomes of ACT-based online treatment for chronic pain (ACTonPain) [ 23 ], and cost-effectiveness analyses revealed that ACTonPain is potentially cost-effective, depending on the amount of society’s willingness to pay [ 24 ]. In this trial, the uptake rate was 97% in both ACTonPain groups, and guided participants completed more modules (0-8) than those who were unguided (mean 5.94, SD 2.80 vs mean 4.74, SD 2.89, F 1,199 =8.92; P <.01).…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized controlled trial (RCT) on an IMI based on Acceptance and Commitment Therapy (ACT) showed guided, but not unguided, IMIs being effective in improving pain interference (Cohen d =0.58 at posttreatment and follow-up, respectively [ 22 ]) in individuals with chronic, nonmalignant pain for 6 months or longer. Moreover, changes in psychological flexibility mediated all outcomes of ACT-based online treatment for chronic pain (ACTonPain) [ 23 ], and cost-effectiveness analyses revealed that ACTonPain is potentially cost-effective, depending on the amount of society’s willingness to pay [ 24 ]. In this trial, the uptake rate was 97% in both ACTonPain groups, and guided participants completed more modules (0-8) than those who were unguided (mean 5.94, SD 2.80 vs mean 4.74, SD 2.89, F 1,199 =8.92; P <.01).…”
Section: Introductionmentioning
confidence: 99%
“…Contents were adapted to the population of people with diabetes from the already evaluated ACTonPain intervention. [49][50][51] The intervention consists of seven modules.…”
Section: Actondiabetes Interventionmentioning
confidence: 99%
“…48 To our knowledge, this is the first study on an ACTbased internet intervention aiming at reducing elevated diabetes distress. Notably, the effectiveness and costeffectiveness of the internet intervention 'ACTonPain' aiming at reducing pain-related burden in people with chronic pain were supported in studies by Lin et al [49][50][51] ACTonDiabetes was built on the ACTonPain treatment programme to develop a widely practicable, local and temporal flexible, low-threshold internet intervention to reduce diabetes distress in people with type 1 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…We identified no other reviews on group PMPs that include synchronous VC. Literature related to online or web-based PMPs that explore self-directed online resources, sometimes coupled with individual appointments or text contact with healthcare professionals has been published [22][23][24].…”
Section: Comparison With Other Reviewsmentioning
confidence: 99%